2022
DOI: 10.1177/08862605221092349
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Coercion and Intimate Partner Violence Victimization Among a Racially and Ethnically Diverse Young Adult Sample

Abstract: Reproductive coercion is an understudied form of intimate partner violence (IPV) that occurs when a person attempts to control the autonomous reproductive decision making of their intimate partner. Previous research has demonstrated that individuals who experience reproductive coercion are more likely to experience other forms of IPV (e.g., physical and sexual). Research has also shown that Black/African American and Latinx/Hispanic individuals are at an increased risk of experiencing reproductive coercion com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Participants who had experienced reproductive coercion were more likely to report physical or sexual, but not psychological, IPV as compared with those who did not experience reproductive coercion. In addition, Hispanic and Latinx participants had a significantly higher prevalence of reproductive coercion when compared with White/non-Hispanic participants (Muñoz et al, 2023).…”
Section: Pressure In Contraception Usementioning
confidence: 95%
See 1 more Smart Citation
“…Participants who had experienced reproductive coercion were more likely to report physical or sexual, but not psychological, IPV as compared with those who did not experience reproductive coercion. In addition, Hispanic and Latinx participants had a significantly higher prevalence of reproductive coercion when compared with White/non-Hispanic participants (Muñoz et al, 2023).…”
Section: Pressure In Contraception Usementioning
confidence: 95%
“…The review also found reproductive coercion disproportionately impacted women experiencing IPV, multiracial women, and women of lower SES; however, the majority of the extant literature was descriptive (Grace & Anderson, 2018). A recent study in Texas investigating reproductive coercion and IPV victimization in a racially diverse sample of female-identified individuals (28.9% White/non-Hispanic, 32.7% Latinx/Hispanic, 25.7% Black/African American, 4.6% Asian/Pacific-Islander, and 8.1% more than one race) aged 19-22 years found 10% of the entire sample had experienced pregnancy coercion and 3.3% has experienced birth control sabotage in their lifetime (Muñoz et al, 2023). Participants who had experienced reproductive coercion were more likely to report physical or sexual, but not psychological, IPV as compared with those who did not experience reproductive coercion.…”
Section: Pressure In Contraception Usementioning
confidence: 99%
“…Data on self-reports reports of reproductive coercion rely on clinic- and/or community-based samples, and the wide variation in estimates are likely attributed to a lack of definitional and conceptual clarity, which has led to heterogeneity in how reproductive coercion has been defined and measured across studies (Grace & Anderson, 2018; Tarzia & Hegarty, 2021). Furthermore, reports of reproductive coercion are greater among racial and ethnic minority groups (Grace & Anderson, 2018; Hill et al, 2019; Holliday et al, 2017; Rosenfeld et al, 2018; Samankasikorn et al, 2019), people who are younger (e.g., less than 30 years) (Grace & Anderson, 2018; Muñoz et al, 2022; Rosenfeld et al, 2018; Samankasikorn et al, 2019), single or not married (Grace & Anderson, 2018; Rosenfeld et al, 2018; Samankasikorn et al, 2019), and with less education (e.g., less than a high school education) (Grace & Anderson, 2018; Samankasikorn et al, 2019). Understanding the interplay between reproductive coercion and reproductive health may strengthen efforts to support autonomous and informed sexual and reproductive health decisions and to prevent violence.…”
Section: Introductionmentioning
confidence: 99%
“…A study of women presenting for routine obstetrics and gynecology care at a clinic in Rhode Island revealed that 32% of the 103 women who reported any type of reproductive coercion also reported they experienced physical or sexual IPV within the same relationship (Clark et al, 2014). Furthermore, some studies have shown that reproductive coercion is positively associated with physical IPV victimization among sexually active undergraduate women (Katz et al, 2017), sexually active female youth (McCauley et al, 2014), female young adults (Muñoz et al, 2022), and people with a recent live birth (Samankasikorn et al, 2019). Together, these findings suggest that reproductive coercion and other forms of IPV are related, and tthis coercion can occur without other forms of physical, sexual, or emotional IPV.…”
Section: Introductionmentioning
confidence: 99%
“…high-income versus low-ormiddle-income countries) [11]. There is somewhat clearer data on the outcomes of RCA, with studies suggesting that it is associated with a range of harmful impacts including unintended pregnancies [2], sexually transmitted infections [12], poor pregnacy outcomes [13] and mental health conditions such as anxiety, post-traumatic stress and depression [14][15][16][17]. As yet, however, there has been little nuance in how these findings have been reported, with RCA treated largely as an homogenous entity, with no distinction being made between pregnancy promoting or pregnancy preventing behaviours.…”
Section: Introductionmentioning
confidence: 99%